A Pro-Tumorigenic Effect of Heparanase 2 (Hpa2) in Thyroid Carcinoma Involves Its Localization to the Nuclear Membrane - Margulis, Itai; Naroditsky, Inna; Gross-Cohen, Miriam; Ilan, Neta; Vlodavsky, Israel; Doweck, Ilana (Frontiers in Oncology, 2021)
Activity of the endo-beta-glucuronidase heparanase, capable of cleaving heparan sulfate (HS), is most often elevated in many types of tumors, associating with increased tumor metastasis and decreased patients’ survival. Heparanase is therefore considered to be a valid drug target, and heparanase inhibitors are being evaluated clinically in cancer patients. Heparanase 2 (Hpa2) is a close homolog of heparanase that gained very little attention, likely because it lacks HS-degrading activity typical of heparanase. The role of Hpa2 in cancer was not examined in detail. In head and neck cancer, high levels of Hpa2 are associated with decreased tumor cell dissemination to regional lymph nodes and prolonged patients’ survival, suggesting that Hpa2 functions to attenuate tumor growth. Here, we examined the role of Hpa2 in normal thyroid tissue and in benign thyroid tumor, non-metastatic, and metastatic papillary thyroid carcinoma (PTC) utilizing immunostaining in correlation with clinicopathological parameters. Interestingly, we found that Hpa2 staining intensity does not significantly change in the transition from normal thyroid gland to benign, non-metastatic, or metastatic thyroid carcinoma. Remarkably, we observed that in some biopsies, Hpa2 is accumulating on the membrane (envelop) of the nucleus and termed this cellular localization NM (nuclear membrane). Notably, NM localization of Hpa2 occurred primarily in metastatic PTC and was associated with an increased number of positive (metastatic) lymph nodes collected at surgery. These results describe for the first time unrecognized localization of Hpa2 to the nuclear membrane, implying that in PTC, Hpa2 functions to promote tumor metastasis.